2010
DOI: 10.1111/j.1532-5415.2010.03170.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Nursing Home Residents with Advanced Dementia

Abstract: OBJECTIVES To examine quality of life (QOL) in nursing home (NH) residents with advanced dementia and identify correlates of QOL near the end of life. DESIGN Cross-sectional data derived from NH records, interviews with residents’ surrogate decision-makers, QOL ratings by NH caregivers, and assessment of residents’ cognitive function. SETTING Three NHs in Maryland. PARTICIPANTS A cohort of NH residents with dementia (n=119), who were either receiving hospice or palliative care or met hospice criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 24 publications
2
70
2
Order By: Relevance
“…In a sample of Italian older home-care patients, reporting chronic daily pain, 34% received any analgesic drug, while only 26% of subjects with dementia received the treatment, with an adjusted odds ratio of 0.80 (95% CI 0.69-0.93) [Landi et al 2001]. However, analgesia is associated with better proxy-rated QoL, measured with ADRQL, in nursing home patients with advanced dementia [Cordner et al 2010]. This is in agreement with the results of a randomized, double-blind, placebo-controlled, crossover trial, which has shown that the administration of paracetamol 3 g/day to patients with moderate to severe AD in nursing homes results in increased social interaction and engagement with environment versus patients who received placebo [Chibnall et al 2005].…”
Section: Analgesicsmentioning
confidence: 98%
“…In a sample of Italian older home-care patients, reporting chronic daily pain, 34% received any analgesic drug, while only 26% of subjects with dementia received the treatment, with an adjusted odds ratio of 0.80 (95% CI 0.69-0.93) [Landi et al 2001]. However, analgesia is associated with better proxy-rated QoL, measured with ADRQL, in nursing home patients with advanced dementia [Cordner et al 2010]. This is in agreement with the results of a randomized, double-blind, placebo-controlled, crossover trial, which has shown that the administration of paracetamol 3 g/day to patients with moderate to severe AD in nursing homes results in increased social interaction and engagement with environment versus patients who received placebo [Chibnall et al 2005].…”
Section: Analgesicsmentioning
confidence: 98%
“…There is a growing consensus that the individual QoL of patients with dementia is an important outcome for effective intervention. Self-ratings are a preferable means to measure the QoL of most dementia patients capable of appraising their own QoL; however, it remains a challenge in advanced dementia patients who are not able to communicate their perspective [35]. …”
Section: Discussionmentioning
confidence: 99%
“…There is even talk of a syndrome specific to institutionalisation which is characterised by symptoms such as apathy and indifference, a decrease in cognitive capacity, difficulties in expressing feelings, loss of autonomy, etc. (29) as well as the importance of a perception of control and the negative effect during the settling-in period of a sense of lack of personal control on one's surroundings (13,17) .…”
Section: Rev Esc Enfermmentioning
confidence: 99%
“…The 6 th European Conference of Health Ministers also called for autonomy to be recognized as an essential factor in personal dignity (17) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation